Growth and β-galactosidase synthesis in aerobic chemostat cultures of Kluyveromyces lactis - Inchaurrondo, V. A. (1998)
Growth and β-galactosidase (β-gal) expression were characterized in the yeast Kluyveromyces lactis strain NRRL Y-1118 growing in aerobic chemostat cultures under carbon, nitrogen or phosphate limitation. In lactose or galactose-limited cultures, β-gal accumulated in amounts equivalent to 10-12% of the total cell protein. The induced β-gal expression was repressed when cells were grown under N- or P-limitation. In lactose medium, enzyme levels were 4-8 times lower than those expressed in C-limited cultures. A similar response was observed when galactose was the carbon source. These results suggest that a galactose-dependent signal (in addition to glucose) may have limited induction when cells were grown in carbon-sufficient cultures. Constitutive β-gal expression was highest in lactate-limited and lowest in glucose-limited media and was also repressed in glucose-sufficient cultures. Other K. lactis strains (NRRL Y-1140 and CBS 2360) also showed glucose repression (although with different sensitivity) under non-inducing conditions. We infer that these strains share a common mechanism of glucose repression independent of the induction pathway. The kinetics of β-gal induction observed in C-limited cultures confirms that β-gal induction is a short-term enzyme adaptation process. Applying a lactose pulse to a lactose-limited chemostat culture resulted in 'substrate-accelerated death'. Immediately after the pulse, growth was arrested and β-gal was progressively inactivated. Yeast metabolism in C-limited cultures was typically oxidative with the substrate being metabolized solely to biomass and CO 2 . Cells grown under P- or N-limitation, either with glucose or lactose, exhibited higher rates of sugar consumption than C-limited cells, accumulated intracellular reserve carbohydrates and secreted metabolic products derived from the glycolytic pathway, mainly glycerol and ethanol.